2020
DOI: 10.5811/cpcem.2020.3.46481
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hyperkalemia Versus Pseudohyperkalemia in Chronic Lymphocytic Leukemia

Abstract: Introduction: Both hyperkalemia and pseudohyperkalemia occur in the emergency department. True hyperkalemia necessitates emergent treatment while pseudohyperkalemia requires recognition to prevent inappropriate treatment. It is imperative that the emergency physician (EP) have an understanding of the causes and clinical presentations of both phenomena. Case Report: We present a case of an 88-year-old male with chronic lymphocytic leukemia (CLL) and suspected blast crisis who was found to have elevated serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, Ranjitkar et al who included adults and multiple leukaemia variants, reported a 50 x10 9 /L leukocyte threshold above which patients were at risk for pseudohyperkalemia, which is not that different from the present study’s threshold, albeit somewhat lower ( 4 ). This lower threshold may be the result of the inclusion of a relatively large number of patients with chronic lymphocytic leukaemia, a leukaemia variant associated with leukocyte fragility ( 2 , 4 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ranjitkar et al who included adults and multiple leukaemia variants, reported a 50 x10 9 /L leukocyte threshold above which patients were at risk for pseudohyperkalemia, which is not that different from the present study’s threshold, albeit somewhat lower ( 4 ). This lower threshold may be the result of the inclusion of a relatively large number of patients with chronic lymphocytic leukaemia, a leukaemia variant associated with leukocyte fragility ( 2 , 4 , 8 ).…”
Section: Discussionmentioning
confidence: 99%